2021
DOI: 10.1016/j.est.2021.102563
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a K2CO3-based thermochemical energy storage system using a honeycomb structured heat exchanger

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In recent years, the interest shifted from purely fundamental to application-oriented [4,5]. The interest in potassium carbonate sesquihydrate has followed similar development, where recently, it has been extensively studied as a thermochemical heat storage material [6][7][8][9][10]. Many other concepts and materials are available for heat storage applications [11] and the category of reversible reactions between salt and water vapour, is just one of the approaches under development [12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the interest shifted from purely fundamental to application-oriented [4,5]. The interest in potassium carbonate sesquihydrate has followed similar development, where recently, it has been extensively studied as a thermochemical heat storage material [6][7][8][9][10]. Many other concepts and materials are available for heat storage applications [11] and the category of reversible reactions between salt and water vapour, is just one of the approaches under development [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some work embedded the heat exchanger into the bed to improve the heat and mass transfer performance, and the results showed that optimizing the total plate area can improve the mass transfer, such as the larger plate radius and larger distance between the plates in the fin plate heat exchanger [256]. Applying and developing a three-dimensional numerical model (Figure 22) for the adsorption reaction of K 2 CO 3 , Kant et al [257] demonstrated that the geometrical parameters of the reactor seriously affected the reaction rate and heat transport in the bed, and better heat transport was obtained by reducing the size of the honeycomb heat exchanger up to a certain level and improving the reaction rate. An open system was investigated experimentally with a mesoporous honeycomb element based on TCES composite materials by CaCl 2 /LiCl filling into Wakkanai siliceous shale (WSS) (Figure 23).…”
Section: Thermal Conductivity Of the Host Matrixmentioning
confidence: 99%
“…Figure22. Schematic of the geometry of the bed: (a) TCM energy storage system, (b) side view of honeycomb heat exchanger filled with TCM, (c) computational domain[257]: Reprinted with permission from Ref [257]. Copyright © 2021 Elsevier Ltd. All rights reserved.…”
mentioning
confidence: 99%
“…In the same line of study, Kant et al 25 developed a numerical prediction model of the performance of the thermochemical energy storage system combined with a honeycomb composite structure filled with potassium carbonate material that can store thermal energy. The study found both honeycomb cell size and thickness of the fins lead to decreeing in the heat transfer through the bed.…”
Section: Introductionmentioning
confidence: 99%